Descriptive Study of Caseworkers' Practices to Support the Development of Self‐Determination of Adults With Intellectual Disabilities. Issue 1 (25th March 2018) - Caouette, Martin; Lachapelle, Yves; Moreau, Jocelyne; Lussier‐Desrochers, Dany
Abstract: Few studies pertain to caseworkers and their practices for supporting the development of self‐determination of adults with intellectual disabilities (ID). This research thus aims at describing the intervention practices of 12 caseworkers from Quebec (Canada). These caseworkers participated in five discussion groups over an 8‐month period. The data analysis helped identify a set of interventions conducted with people who have ID and with their environments. The majority of interventions are person‐specific, although natural and foster families are also targets for intervention. A number of person‐specific and environment‐specific variables influence these interventions. These variables concern people with ID, caseworkers, natural families, foster families, service organizations, and the community. The complexity of the intervention process is discussed. Recommendations are formulated for caseworkers, service organizations, and public decision makers.